Myth, image, dianoia: Situating the myth of Er on the Divided Line - Woloshyn, Cameron (University of Ottawa (Canada), 2009)
Perennially, investigations into Plato's use of myths have hinged on a distinction between muthos and logos, from which logos is privileged as philosophical discourse, while muthoi are relegated to tools of persuasion for the non-philosophical. Focussing exclusively on the Republic, this thesis argues that Plato's myths can constitute a necessary, although not a sufficient component of Plato's philosophical discourse. In his discussion of the section of dianoiu in the Divided Line, Plato writes: "the soul, using as images the things that were imitated before, is forced to investigate from hypotheses, proceeding not to a first principle but to a conclusion (510b4-6)." Elaborating on this passage, I shall demonstrate how dianoetic understandings rely on the collaboration of both images and argument. I argue that Plato presents the Myth of Er as a dianoetic image, on which Plato's arguments concerning the justice rely.
Keywords: Philosophy.